Health and economic outcomes of 20-valent pneumococcal conjugate vaccine compared to 15-valent pneumococcal conjugate vaccine strategies for adults in Greece - Gourzoulidis, George; Barmpouni, Myrto; Kossyvaki, Vasiliki; Vietri, Jeffrey; Tzanetakos, Charalampos (Frontiers in Public Health, 2023)
Objective Higher valency pneumococcal conjugate vaccines (PCVs) are expected to improve protection against pneumococcal disease through coverage of additional serotypes. The aim of the present study was to evaluate the cost-effectiveness of 20-valent pneumococcal conjugate vaccine (PCV20) compared to 15-valent pneumococcal conjugate vaccine (PCV15) alone or followed by 23-valent polysaccharide vaccine (PPV23) for adults in Greece. Methods A published Markov model was adapted to simulate lifetime risk of clinical and economic outcomes from the public payer’s perspective. The model population was stratified based on age and risk profile (i.e., low, moderate, or high-risk of developing pneumococcal disease). Epidemiologic parameters, serotype coverage and vaccines’ effectiveness were based on published literature, while direct medical costs (prices €, 2022) were obtained from official sources. Main model outcomes were projected number of invasive pneumococcal disease (IPD) and all-cause non-bacteremic pneumonia (NBP) cases and attributable deaths, costs and quality-adjusted life-years (QALY) for each vaccination strategy. Sensitivity analyses were performed to ascertain the robustness of model results. Results Over the modeled time horizon, vaccination with PCV20 compared to PCV15 alone or PCV15 followed by PPV23 prevents an additional 747 and 646 cases of IPD, 10,334 and 10,342 cases of NBP and 468 and 455 deaths respectively, resulting in incremental gain of 1,594 and 1,536 QALYs and cost savings of €11,183 and €48,858, respectively. PSA revealed that the probability of PCV20 being cost-effective at the predetermined threshold of €34,000 per QALY gained was 100% compared to either PCV15 alone or the combination of PCV15 followed by PPV23. Conclusion PCV20 is estimated to improve public health by averting additional pneumococcal disease cases and deaths relative to PCV15 alone or followed by PPV23, and therefore translates to cost-savings for the public payer. Overall results showed that vaccination with PCV20 was estimated to be a dominant vaccination strategy (improved health outcomes with reduced costs) over PCV15 alone or followed by PPV23 for prevention of pneumococcal disease in adults in Greece.